BIOMASS AND CARBON IN NON-WOODY VEGETATION, DEAD WOOD AND LITTER IN IGUAÇU NATIONAL PARK - Sanquetta, Carlos Roberto; Corte, Ana Paula Dalla; Pinto, Caciane; Melo, Luiz Antônio Nunes (Floresta, 2014)
This study was carried out in 2004 in Iguacu National Park (INP), Paraná-Brazil. The vegetation is composed of Araucaria Forest (AF) (13.1%) and Seasonal Semi-deciduous Forest (FES) (86.9%). Two types of materials were analyzed: litter (L) and woody material (W) (alive (A) and dead (D)), and classified by diameter: W1(0–0.70 cm), W2(0.71–2.5 cm), W3(2.51–7.50 cm), and W4(³7.5 cm). The results for the FES was 21.7 t/ha, with 42.4% in diameter class WD4 (8.98 t/ha) and 38.6% was litter (8.17 t/ha). The FOM was 12.87 t/ha, with 78.9% litter. The carbon stocks of the materials varied between 36.2% and 42.1% (for litter and WD4), both in the FES. There were no significant differences between the carbon stocks of the forest types. Rather differences existed between the pools (5% ANOVA and Tukey test). In the FES the carbon stock was 8.29 t/ha, which is equivalent to 30.41 tCO2e/ha, and in the FOM the stock was 4.94t/ha or 18.12 tCO2e/ha. For the vegetation types the carbon stock in INP was 8.35 tC/ha and 30.62 tCO2e/ha for the FES and FOM, respectively. The carbon pools analyzed in this study contribute significantly to the total carbon stock of a forest ecosystem and should always be taken into consideration when developing estimates for a forest. Keywords: Araucaria; Seasonal Semideciduous Forest; Araucaria Forest; climate change; carbon fraction. Resumo Biomassa e carbono na vegetação não arbórea, madeira morta e serapilheira no Parque Nacional do Iguaçu. O trabalho ocorreu em 2004 no Parque Nacional do Iguaçu (PNI), Paraná. O PNI tem Floresta Ombrófila Mista (FOM) (13,1%) e Floresta Estacional Semidecidual (FES) (86,9%). Foram analisados L – serapilheira e W – materiais lenhosos (vivos – A e mortos – D), classificados pelos diâmetros: W1 (0 a 0,70 cm), W2 (0,71 a 2,5 cm), W3 (2,51 a 7,50 cm) e W4 (³7,51 cm). Os resultados da FES mostram 21,7 t.ha-1, sendo 42,4% do WD4 (8,98 t.ha-1) e 38,6% da serapilheira (8,17 t.ha-1). Na FOM, foram 12,87 t.ha-1 (78,9%) da serapilheira. Os teores de carbono dos materiais variaram de 36,2 a 42,1% (para serapilheira e WD4), ambos na FES. Não houve diferenças significativas nos teores de carbono, havendo diferença nos compartimentos (5% ANOVA) e teste de Tukey. Na FES, o estoque de carbono foi 8,29 t.ha-1, correspondendo a 30,41 tCO2e.ha-1, e na FOM de 4,94 tC.ha-1 e 18,12 tCO2e.ha-1. Para as fitofisionomias, o estoque de C no INP foi de 8,35 tC.ha-1 e 30,62 tCO2e.ha-1. Os reservatórios de C analisados no estudo apresentam participação importante no estoque total de C do ecossistema florestal, devendo sempre serem considerados quando do desenvolvimento de estimativas para a floresta. Palavras-chave: Araucária; Floresta Estacional Semidecidual; Floresta Ombrófila Mista; mudanças climáticas; teor de carbono.